Natural and Artificial Regeneration of Boswellia papyrifera in the Blue Nile State – Sudan - Gessmalla, Ammar Fadlalla; Raddad, Elamin Yousif A. (University of Khartoum Journal of Agricultural Sciences, 2023)
Boswellia papyrifera is an important resource in the dryland of the Blue Nile State. However, its population is declining due to many biological and environmental factors. Moreover, there was hardly any regeneration of the species in its natural habitat. The objectives of this study were to count the new regeneration of seedlings, before and after rainfall, to assess the viability of B. papyrifera seeds in the soil seed bank, to detect the effect of soil types on seedlings’ growth and to determine the optimum diameter and time of cutting. Natural regeneration surveys were carried out in the field by counting the young seedlings at different elevations before and after the rains. Soil samples from plots 2x2 metres were randomly collected. B. papyrifera seeds were sown in two types of soil mixes namely, 1 sand: 2 silt by volume; and in soil collected from the site where B. papyrifera trees are growing. Branch cuttings of one meter length and 4-5cm and 6-7cm in diameter, each, were taken at three different dates, namely first of April, mid of April and first of May and planted in the nursery. The results showed that B. papyrifera produced plenty of seeds that were stored in the soil seed bank. However, seedlings were almost absent after the dry season. A significant (P<0.05) difference was found between the mean number of seedlings growing at the foot of the mountain and the slope as compared to those growing on top of the mountain. A significant (P≤0.05) difference was found between the mean height of seedlings raised in the two types of soils. There was no significant difference between the number of survived branch cuttings due to planting date and/or branch diameter, but large diameter cuttings showed better results. These results suggest that additional management interventions, such as artificial regeneration, to support early seedlings